5 - La conférence nationale souveraine et la démocratisation au Togo du point de vue de la société civile: 10.4314/ad.v25i3.22105 - Iwata, Takuo (Africa Development, 2000)
The aim of this article is to analyse the process of democratic transition instituted by the Sovereign National Conference (SNC) in Togo, from the standpoint of the notion of civil society. In Togo, despite the authoritarian regime instituted by General Eyadema has remained in power since 1967, the Togolese had lived a period of hope when there had a beginning of democratic transition initiated by the SNC. The SNC is the result of the maturity of citizens associations, which had opened positive perspectives for the future of politics in this country. This conference has been of great importance in the political history of Africa.This study proposes to analyse the démocratisation process in Togo from the standpoint of the SNC. But it also aims at thinking of the démocratisation of other African countries, especially those who have organised a SNC, and studying the relationship between African policy and the notion of civil society.